Magnesium Picolinate Improves Bone Formation by Regulation of RANK/RANKL/OPG and BMP-2/Runx2 Signaling Pathways in High-Fat Fed Rats - Sahin, Emre; Orhan, Cemal; Balci, Tansel Ansal; Erten, Fusun; Şahin, Kazım (Mdpi, 2021)
Magnesium (Mg) deficiency may affect bone metabolism by increasing osteoclasts, decreasing osteoblasts, promoting inflammation/oxidative stress, and result in subsequent bone loss. The objective of the present study was to identify the molecular mechanism underlying the bone protective effect of different forms of Mg (inorganic magnesium oxide (MgO) versus organic magnesium picolinate (MgPic) compound) in rats fed with a high-fat diet (HFD). Forty-two Wistar albino male rats were divided into six group (n = 7): (i) control, (ii) MgO, (iii) MgPic, (iv) HFD, (v) HFD + MgO, and (vi) HFD + MgPic. Bone mineral density (BMD) increased in the Mg supplemented groups, especially MgPic, as compared with the HFD group (p < 0.001). As compared with the HFD + MgO group, the HFD + MgPic group had higher bone P (p < 0.05) and Mg levels (p < 0.001). In addition, as compared to MgO, MgPic improved bone formation by increasing the levels of osteogenetic proteins (COL1A1 (p < 0.001), BMP2 (p < 0.001), Runx2 (p < 0.001), OPG (p < 0.05), and OCN (p < 0.001), IGF-1 (p < 0.001)), while prevented bone resorption by reducing the levels of RANK and RANKL (p < 0.001). In conclusion, the present data showed that the MgPic could increase osteogenic protein levels in bone more effectively than MgO, prevent bone loss, and contribute to bone formation in HFD rats.
Keywords: magnesium picolinate; bone; bone mineral density; osteogenic proteins; high-fat diet